In-game Social Interaction and Gaming Disorder: A Perspective From Online Social Capital - Heng, Shupeng; Zhao, Huanfang; Wang, Minghui (Frontiers in Psychiatry, 2021)
Background and aims: Social interaction in the online games has been found to predict problematic online gaming (POG), but little research has examined the mechanism of this association. Drawing on the social capital theory, the present study investigated the mediating role of online social capital on the relationship between in-game social interaction and POG, and the moderating role of alienation on the relationship between online social capital and POG. Methods: A sample of 457 Chinese MMORPG gamers was recruited to complete the In-Game Social Interaction Questionnaire, Online Social Capital Scale, Alienation Scale and Pathological-Gaming Scale. Results: The results showed online social capital was a mediator in the relationship between in-game social interaction and POG. Moreover, for individuals with low alienation, the effect of online social capital on POG was weaker than for those with high alienation. Conclusions: The present study provides new insight into the complex processes involved in the effect of in-game social interaction on POG, and the results have important theoretical and practical implications.